The Problematic Issues of Sports Law in Latvia: Compliance of Labour and Tax Legislations from the Sustainable Development Perspective - Zalcmane, Karina; Kamenecka-Usova, Marina; Bickovskis, Atis (European Journal of Sustainable Development, 2021)
Sport performs several functions in society: an educational, a social, a cultural as well as a recreational function. Nevertheless, sport is also a business: in economic terms, it is a rapidly growing area accounting for 3% of world trade and is one of the sectors most likely to generate new employment in the near future (Colucci & Hendrickx, 2014). For that reason, at the present stage of sustainable development of sports in Europe in general and in Republic of Latvia in particular, there is a growing need for a clear regulation of the employment relations of professional athletes and transparency of taxation in the sports industry. Taking these considerations into accounts, aim of the research paper is to assess the theoretical and practical issues related to employment relationships and taxation in Latvian sports from the sustainable development perspective. The methodological basis of the research consists of general scientific and special legal research methods.